Pro-inflammatory cytokines in patients with chronic kidney disease: interleukin-6 in focus - I. T. Murkamilov; K. A. Aitbae; V. V. Fomin; Zh. A. Murkamilova; I. S. Sabirov; Z. R. Rayimzhanov; N. A. Redzhapova; F. A. Yusupov (Архивъ внутренней медицины)
Objective of the study. To assess the clinical and pathogenetic significance of serum interleukin-6 (IL-6) in patients with chronic kidney disease.Materials and methods. A cross-sectional study enrolled 288 patients with chronic kidney disease (CKD) aged 16 to 86 years, average age (54.5 ± 14.5) years. The study enrolled 146 (50.7%) women and 142 (49.3%) men. Depending on the value of estimated glomerular filtration rate (eGFR), all the examined patients were divided into two groups: 1st (n = 154) - persons with eGFR > 60 ml/min; 2nd (n = 134) - patients with eGFR < 60 ml/min, i.e. renal failure. CKD was identified when there was evidence of damaged and/or reduced renal function. Glomerular filtration rate was calculated using the Hoek equation based on measurement of serum cystatin C, and severity of CKD was based on eGFR values. All patients had concentration of creatinine, cystatin C and IL-6 in their blood serum studied.Results. In the 2nd group of patients with eGFR below 60 ml/min, average age [(57.9 ± 14.5) years vs. (51.6 ± 13.9) years; p < 0.05], systolic blood pressure [(142 ± 24) mm Hg vs. (133 ± 22) mm Hg; p < 0.05], cystatin C [1.815 (1.430-3.070) mg/l vs. 0.980 (0.900-1.100) mg/l; p < 0.05)] and IL-6 [2.761 (1.400-6.495) pg/ml vs. 1.754 (0.849-3.226) pg/ml; p < 0.05)] levels in blood serum were significantly higher compared with the 1st group. An inverse correlation was found between serum IL-6 and eGFR level (r = -0.144; p = 0.018).Conclusion. In patients with chronic kidney disease with an eGFR level below 60 ml/min, an increase in systolic blood pressure and serum IL-6 concentration was observed. In chronic kidney disease, an increase in the content of IL-6 was accompanied by a decrease in glomerular filtration rate and an increase in diastolic blood pressure.